A Puzzle of Vestibular Physiology in a Meniere's Disease Acute Attack. (18th June 2015) - Martinez-Lopez, Marta; Manrique-Huarte, Raquel; Perez-Fernandez, Nicolas
Abstract : The aim of this paper is to present for the first time the functional evaluation of each of the vestibular receptors in the six semicircular canals in a patient diagnosed with Meniere's disease during an acute attack. A 54-year-old lady was diagnosed with left Meniere's disease who during her regular clinic review suffers an acute attack of vertigo, with fullness and an increase of tinnitus in her left ear. Spontaneous nystagmus and the results in the video head-impulse test (vHIT) are shown before, during, and after the attack. Nystagmus was initially left beating and a few minutes later an upbeat component was added. No skew deviation was observed. A decrease in the gain of the vestibuloocular reflex (VOR) and the presence of overt saccades were observed when the stimuli were in the plane of the left superior semicircular canal. At the end of the crisis nystagmus decreased and vestibuloocular reflex returned to almost normal. A review of the different possibilities to explain these findings points to a hypothetical utricular damage.